Strategi Pengembangan Kepemimpinan Kepala Sekolah untuk Meningkatkan Kinerja Guru - Hafizah Wichayani Rawi; Nur Ainun; Syavira Rachman; Nurhayati Harahap; Dewi Purnama; Tara Latifa; Zachra; Inom Nasution (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this research is to find out how school principals' leadership development strategies can improve teacher performance. This research uses the library research method. The results of this research indicate that the principal's leadership development strategy to improve teacher performance is policy programs created by the principal with the aim of improving teacher performance. The role of the principal in providing motivation, direction and encouragement as well as supervising teacher performance is also a development strategy so as to provide opportunities for teachers to develop their capacity related to teacher performance assessment. Performance must be achieved by teachers in carrying out their duties of teaching, guiding and training students so that teacher performance is important to evaluate. Suggestions for further research are to use this title by highlighting more phenomenal variables.